OCYS PHOCEUS N. SP., A NEW INTERESTING OROPHILOUS SPECIES OF CENTRAL GREECE (Coleoptera, Carabidae) (*) - Giachino, Pier Mauro; Vailati, Dante (Fragmenta entomologica, 2012)
(*) Results of the programme “Research Missions in the Mediterranean Basin” sponsored by the World Biodiversity Association onlus. XXVIIIth contribution. A new species of Trechinae ground beetles (Coleotera, Carabidae), Ocys phoceus n. sp., is described from Kokkiniás Mt. in the Vardoússia Mts. (Prefecture of Fokída, Greece). Ocys phoceus n. sp. is strictly related, and represents the Western vicariant, of O. rotundipennis Huber and Marggi, 2001, of the Parnassós Mt.